Vegetation, Floristic Composition and Species Diversity in a Tropical Mountain Nature Reserve in Southern Yunnan, SW China, with Implications for Conservation. (June 2015) - Zhu, Hua; Yong, Chai; Zhou, Shisun; Wang, Hong; Yan, Lichun
Complete floristic and vegetation surveys were done in a newly established nature reserve on a tropical mountain in southern Yunnan. Three vegetation types in three altitudinal zones were recognized: a tropical seasonal rain forest below 1, 100 m; a lower montane evergreen broad-leaved forest at 1, 100-1, 600 m; and a montane rain forest above 1, 600 m. A total of 1, 657 species of seed plants in 758 genera and 146 families were recorded from the nature reserve. Tropical families (61%) and genera (81%) comprise the majority of the flora, and tropical Asian genera make up the highest percentage, showing the close affinity of the flora with the tropical Asian (Indo-Malaysia) flora, despite the high latitude (22°N). Floristic changes with altitude are conspicuous. The transition from lowland tropical seasonal rain forest dominated by mixed tropical families to lower montane forest dominated by Fagaceae and Lauraceae occurs at 1, 100-1, 150 m. Although the middle montane forests above 1, 600 m have 'oak-laurel' assemblage characteristics, the temperate families Magnoliaceae and Cornaceae become dominant. Both the tree species diversities and the numbers of genera and families are higher in the lowlands and middle montane zones than in the lower montane. The lower diversity in the lower montane zone could reflect less precipitation and frequent fires in the historical past. The species compositions of samples within each altitudinal zone show greater horizontal turnover (β diversity) in the lowlands. Conservation efforts should focus on the species-rich lowland and middle montane forests.